Per-operative evaluation of destructive pattern of COVID associated rhinocerebral mucormycosis - Sachdeva, Kavita; Saji, Tinnu Anna (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: The rapid global spread of Coronavirus disease led to declaration of COVID-19 as a pandemic on March 11,2020. Secondary infections are reportedly common in hospitalized, severely ill COVID-19 patients, encompassing between 10 and 30% of cases, fungal being 10 times more common. Mucormycosis is amongst the most fulminant form of zygomycosis caused by mucorales species of the phylum zygomycota and currently referred as COVID associated mucormycosis (CAM). The aim of this study is to evaluate the extend and pattern of destruction in nose, paranasal sinus and orbit found during the surgical debridement of post COVID hyperglycemic patients of mucormycosis. Methods: This prospective observational study was done on a random sample of 86 patients who came to ENT OPD of a tertiary care centre of middle India with clinical, radiological or histological findings suggestive of CAM. These patients underwent aggressive surgical debridement followed by antifungals and strict control of diabetic mellitus. The extend and pattern of destruction caused by CAM in nose, paranasal sinus and orbit noticed peroperatively were analysed. Results: Out of the 86 patients who got operated, there are 62 males and 24 females patients aged from 28 to 86 years. The left side was involved in 41 patients, and the right side in 66 patients. Among the nasal involvement, middle turbinate (56) was maximally involved followed by inferior turbinate (52), superior turbinate (1), septum (17) with posterior septum mostly involved, floor of nose was involved in (4) patients. The orbit was involved in 28 cases in which lamina papyracea was eroded in all cases followed by inferior orbital wall, orbital muscles, optic nerve. Cribriform plate was eroded in 3 patients. The overall extent of involvement of mucormycosis is as follows maxilla (86), ethmoid (71), frontal (29), sphenoid (30), septum (17), orbit (28), alveolus (5), palate (10), intracranial (9), subcutaneous phycomycosis (10). Conclusions: Management of CAM is really challenging which needs a multidisciplinary approach that includes aggressive surgical debridement, aggressive medical therapy with Amphotericin B and correction of the predisposing factors primarily diabetics mellitus